Historical dictionary of air intelligence - Trenear-Harvey, Glenmore S., 1940- (Lanham, Md. : Scarecrow Press, 2009)
The Historical Dictionary of Air Intelligence relates the evolving history of the rapidly advancing field of air intelligence. A chronology, an introductory essay, and cross-referenced dictionary entries on the agencies, agents, operations, equipment, tradecraft, and jargon of air intelligence make this reference as essential as it is fascinating.--Publisher's description.
Includes bibliographical references (pages 211-218).
Keywords: Geschichte; Aerial reconnaissance -- History -- Dictionaries; Military intelligence -- History -- Dictionaries; Dictionary